The Primacy of Climate Change for Sustainable International Tourism. (17th April 2013) - Hall, C. Michael; Scott, Daniel; Gössling, Stefan; Springett, Delyse
ABSTRACT International tourism is portrayed by many agencies and governments as a significant contributor to sustainable development strategies. The economic impacts of international tourism are undoubtedly substantial; however, they need to be framed within a broader understanding of impacts throughout the tourism system. Emissions from tourism and their contribution to climate change therefore set a potentially major challenge for the sustainability of international tourism. Following an examination of the current and forecast growth of emissions from international tourism and the policies and strategies of lead bodies, industry and national governments, tourism is seen as grounded in a pro‐growth paradigm that offers no hope within the foreseeable future of absolute reductions in emissions. Given the potential implications of this finding, it is concluded that a significant reassessment is required of the potential benefits of tourism for sustainable development. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment